(untitled) (Journal of Training and Development, 2017)
This paper reflects on my journey from the Nepal to the United Kingdom UK) as a student initially and then as a National Health Service (NHS) Grampian’s employee. The purpose of developing this paper was to draw insights on the factors that pulled me as an urban youth for studying and living in the UK and to present the significance of skills-based technical education for the changing job market. I used analytic autoethnography to carry out this research, where I presented past epiphanies and consecutively interpreted the strong memories of those lived experiences and observations to broaden my theoretical understandings. I argued based on my lived experiences that the scope of the market based technical education is globally prevalent. For this, I have sequentially presented my stories of self-realizations and skills acquisition in the developed country such as the UK from the theoretical ideas of ethnoscapes, new and intelligent urbanism, and credentialism. Moreover, I have illuminated the relevance and significance of market based technical education courses for competing not only in Nepal but also in the global job market of the UK through self-reflection. Findings in this paper suggest the need for the international students to be pre-equipped with market based skills and to opt for market oriented subjects preferably from the field of technical education.